Geophysical Constraints on the Relationship Between Seamount Subduction, Slow Slip, and Tremor at the North Hikurangi Subduction Zone, New Zealand - Daniel H. N. Barker; Stuart Henrys; Fabio Caratori Tontini; Philip M. Barnes; Dan Bassett; Erin Todd; Laura Wallace (Geophysical Research Letters)
Abstract We use a prestack depth migration reflection image and magnetic anomaly data across the northern Hikurangi subduction zone, New Zealand, to constrain plate boundary structure and geometry of a subducting seamount in a region of shallow slow slip and recent International Ocean Discovery Program drilling. Our 3‐D model reveals the subducting seamount as a SW‐NE striking, lozenge‐shaped ridge approximately 40 km long and 15 km wide, with relief up to 2.5 km. This seamount broadly correlates with a 20‐km‐wide gap separating two patches of large (>10 cm) slow slip and the locus of tectonic tremor associated with the September–October 2014 Gisborne slow slip event. Largest slow slip magnitudes occurred where the décollement is underlain by a 3.0‐km‐thick zone of highly reflective subducting sediments. Wave speeds within this zone are 7% lower than adjacent and overlying strata, supporting the view that high fluid pressures within subducting sediments may facilitate shallow slow slip along the north Hikurangi margin.